2001
DOI: 10.1021/jp010351f
|View full text |Cite
|
Sign up to set email alerts
|

Vanadia Gel Synthesis via Peroxovanadate Precursors. 2. Characterization of the Gels

Abstract: Vanadium oxide gels derived from the reaction of H2O2 and V2O5 have been investigated using 51V MAS NMR, TGA, XRD, SEM, and laser Raman spectroscopy. Based primarily on the 51V MAS NMR and TGA results, the coordinations of five distinct vanadia sites have been detailed, which possibly include a previously unreported dimer. The relative concentration of these sites changed as dehydration progressed, and a model of this process has been proposed based on the numerical analysis of the NMR MAS spectra. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
65
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 22 publications
(67 reference statements)
16
65
0
Order By: Relevance
“…VO 3 (OH), (VO 3 ) n , VO 2 (OH) 2 , V 10 O 26 (OH) 2 , VO(OH) 3 , V 10 O 27 (OH), (V 2 O 7 ) 4À , or V 10 O 28 6À , depending on the net surface pH, as was demonstrated using Raman spectroscopy by Deo and Wachs [253]. This agrees with recent 51 V NMR data, which have also shown that surface complexes remain attached to the surface, though not as strongly as in the dehydrated state [148,254,255]. Surface vanadia species in hydrated VO x /SiO 2 are similar to those found in V 2 O 5 AEnH 2 O gels.…”
Section: Catalysissupporting
confidence: 88%
See 3 more Smart Citations
“…VO 3 (OH), (VO 3 ) n , VO 2 (OH) 2 , V 10 O 26 (OH) 2 , VO(OH) 3 , V 10 O 27 (OH), (V 2 O 7 ) 4À , or V 10 O 28 6À , depending on the net surface pH, as was demonstrated using Raman spectroscopy by Deo and Wachs [253]. This agrees with recent 51 V NMR data, which have also shown that surface complexes remain attached to the surface, though not as strongly as in the dehydrated state [148,254,255]. Surface vanadia species in hydrated VO x /SiO 2 are similar to those found in V 2 O 5 AEnH 2 O gels.…”
Section: Catalysissupporting
confidence: 88%
“…In a similar fashion, the structure of the tailor-made macroporous vanadium oxide foams has been examined by 51 V NMR in [244] (Table 5). It has been revealed that the local structure of vanadium sites in these foams is similar to that reported earlier for V 2 O 5 xerogels [148].…”
Section: Materials Chemistrysupporting
confidence: 86%
See 2 more Smart Citations
“…51 V MAS NMR spectra of both initial and hydrogenated films (Figure 11(a)) contain the only signal with isotropic shift around −575 ppm, which corresponds to vanadium in the vanadium pentoxide phase of V 2 O 5 -xerogel [24]. However, the intensity of the signal in hydrogenated film is lower by 2.7 times than in initial one.…”
Section: Vanadium Pentoxidementioning
confidence: 96%